In vitro evaluation of Punica granatum fruit peel extract for its potential anti-diabetic effects - More, Rutuja K; Pingale, Prashant L; Upasani, Chandrashekhar D; Amrutkar, Sunil V (Creative Pharma Assent, 2024)
Background: With growing awareness of pomegranate's health benefits, pomegranate products have been consumed more frequently in recent years, and pomegranate peel has emerged as one of the most prevalent wastes in the food industry. Pomegranate Peel concentrate is an indigenous substance with strong antioxidant and antidiabetic actions as a result of its tannins as well as polyphenols content. Methods: In the present study, pomegranate skin extract, both liquid and alcohol-based, was evaluated for polyphenolic and flavonoid content. Alcoholic fruit peel extract was also assessed for 1,4-α-D-glucan glucanohydrolase and α-D-glucoside glucohydrolase enzyme activity. Results: According to findings, pomegranate peel extract showed significant antioxidant content. Phytochemical analysis of ethanol-derived extract of pomegranate peel found a noteworthy amount of ellagitannins and flavonoids such as Punicalin, Punicalgin, Punicic acid, Catechin, Quercetin, Rutin, and Kaempferol. In contrast, punicalgin, ellagic acid, and gallic acid are responsible for antidiabetic activity. The LC-MS characterization of peel extract of pomegranate showed 10 bioactive compounds. The IC50 value for 80% alcoholic extract of pomegranate peel was found to be 5.86 mg/ml of α- amylase and 6.58 mg/ml of α-glucosidase. Conclusion: It was found that the inhibition of 1,4-α-D-glucan glucanohydrolase and α-D-glucoside glucohydrolase enzymes could be an effective mechanism by which it can give anti-diabetic effects.